Implementasi Demokrasi dalam Otonomi Desa - M Nur Budiyanto (Magister Ilmu Administrasi Publik, 2002)
The village social and political development nowdays tend to show in the uncertain condition and mistrack. On one side, in the rural community there is much basic weakness such as the low degree of human resource, natural resource, culture, financial, and political and the economic infrastructure. The commitment of elite leadership (Village Legislative Body , Head of Village and its personnel) tend to be weak hear the village community aspiration. On other side, the centralgovernment (including localgovernment) articulate that the decentralisation process, democrag and village autonomy is also show the mistrack The attempt to impelement tightly the legislation of the village autonomy that must be obeyed and the legislation homogeni# for at least a district/ city is dearly the betrayal